(untitled) (Andamios, Revista de Investigación Social, 2012)
This article reviews the antinomy tradition / modernity in the constitutive tension of the historical singularity of Cordoba, constituted in two Córdobas —the clerical and the liberal—, estimating this both faces in the relation between culture and politics, which manifests itself in the young intelligentsia intellectuality, auto-recognized as generation of 1914, in whose path places his participation in the movement of the Reforma Universitaria of 1918, in Córdoba.